Role of TNF-α -308G/A gene polymorphism in gastric cancer risk: A case control study and meta-analysis - Du, Li-Chuan; Gao, Ru (Turkish Journal of Gastroenterology, 2017)
Abstract Background/Aims: In the Chinese population, gastric cancer (GC) is ranked as the third most common type of cancer. Although the exact etiology of GC development is unclear, several factors, including genetic and environmental, have been identified as risk factors. Variations in cytokine genes and their receptors have been related to a higher risk of GC. A single nucleotide polymorphism in the promoter region of tumor necrosis factor-α (TNF-α) (-308G>A) has been associated with a higher risk of GC and in the present study we evaluated its possible association with GC in a Chinese cohort. In addition, we performed a meta-analysis to draw a firm conclusion about the association between TNF-α gene polymorphisms and GC. Materials and Methods: We enrolled 400 Chinese GC patients and matched healthy controls hailing from similar geographical areas. The TNF-α -308G/A polymorphism was genotyped by allele-specific polymerase chain reaction (AS-PCR). For the meta-analysis, earlier published articles were searched and eligible studies were included. Results: Prevalence of the heterozygous mutant (GA) and minor allele (A) were significantly higher in GC cases compared to healthy controls (GA: p<0.0001, odds ratio (OR)=4.90; A: p<0.0001, OR=2.84). A total of 36 eligible studies including the present report, encompassing of 8353 GC patients and 12099 controls, were analyzed for the meta-analysis. A significant association of the TNF-α polymorphism (-308G>A) with susceptibility to GC was only found in the Caucasian population (A vs G: p=0.001; AA vs GG: p=0.01; AG vs GG: p<0.0001; AA vs AG+GG: p=0.01; AA+AG vs p=0.003). Conclusion: The results of the present case control study and meta-analysis showed that associations between TNF-a variants with susceptibility to GC development is population and ethnic specific. Cite this article as: Du LC, Gao R. Role of TNF-α -308G/A gene polymorphism in gastric cancer risk: a case control study and meta-analysis. Turk J Gastroenterol 2017; 28: 272-82.